Sex-Related Differences in Innate and Adaptive Immune Responses to SARS-CoV-2 - Agrawal, Sudhanshu; Salazar, Jon; Tran, Thu Michelle; Agrawal, Anshu (Frontiers in Immunology, 2021)
COVID-19 exhibits a sex-bias with males showing signs of more severe disease and hospitalizations compared to females. The mechanisms are not clear but differential immune responses, particularly the initial innate immune response, between sexes may be playing a role. The early innate immune responses to SARS-CoV2 have not been studied because of the gap in timing between the patient getting infected, showing symptoms, and getting the treatment. The primary objective of the present study was to compare the response of DCs and monocytes from males and females to SARS-Cov2 CoV2 24h after infection. To investigated this, PBMCs from healthy young individuals were stimulated in vitro with the virus. Our results indicate that PBMCs from females upregulated the expression of HLA-DR and CD86 on pDCs, and mDCs, and monocytes after stimulation with the virus while the activation of these cells was not significant in males. Monocytes from females also displayed increased activation than males. In addition, females secreted significantly secreted higher levels of IFN-α and IL-29 compared to males at 24h. In contrast, the secretion of these cytokines was not significant in males. However, the situation was reversed at one week post stimulation and males displayed high levels of IFN-α production compared to females. Further investigations revealed that the secretion of CXCL-10, a chemokine associated with lung complications, was higher in males than females at 24h. The PBMCs from females also displayed increased induction of CTLs. Altogether, our results suggest that decreased activation of innate immune cells- pDCs, mDCs and monocytes, the delayed and prolonged IFN-a secretion along with increased CXCL-10 secretion may be responsible for the severity of COVID-19 in males.